PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MULTIPLE INTELLIGENCES PADA MATERI JAMUR KELAS X SMA - Hac D, M. Ulil; Mariani NL, Mariani NL; Nursal, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research into the development of worksheet Students (LKPD) based on multiple intelligences in the material fungi class X High School in the Faculty of Education, University of Riau in January-June 2017. The research relates to research approaches R & D in this study using a model ADDIE developed by Dick and Carry. Research carried out until the stage of development. Research topics were KD 3.7 SMA class X fungi material developed to 5 LKPD for 5 meetings. The data were collected using a validation sheet for 5 person validator, limited testing LAB scale focused 5th semester student who studied the mold material as many as 15 students and limited tests aimed at ninth grade high school students who have studied the mold material filled in. Population and samples for a limited trial arbitrarily determined that MIA IX grade 3 in SMAN 4 Pekanbaru preferably 20 people Students. The results of the validation of aspects of design, pedagogy and content show a fifth LKPD obtaining an average score of 03:43, 03:52, 3,62, 3,67, 3,65 categorized as very valid as long as the test results limited from the viewpoint of design, pedagogy and content to show students the fifth HTPD achieved an average score 3.32, 3.45, 3.40, 3.45, 3.43 with a very good category. While the aspect of design, pedagogical and content in SMA N 4 Pekanbaru students showed that both LKPD achieved an average score of 3.49, 3.48. Based on the results of the data analysis, it showed that the development of multiple intelligences based LKPD has successfully developed and is feasible for use as a reference in learning at school.Keywords: Development, Student Worksheet, Multiple Intelligences